Mobilities of Knowledge - Jöns, Heike; Meusburger, Peter; Heffernan, Michael (Knowledge and Space,, 2017)
This collection of essays examines how spatial mobilities of people and practices, technologies and objects, knowledge and ideas have shaped the production, circulation, and transfer of knowledge in different historical and geographical contexts. Targeting an interdisciplinary audience, Mobilities of Knowledge combines detailed empirical analyses with innovative conceptual approaches. The first part scrutinizes knowledge circulation, transfer, and adaption, focussing on the interpersonal communication process, early techniques of papermaking, a geographical text, indigenous knowledge in exploration, the genealogy of spatial analysis, and different disciplinary knowledges about the formation of cities, states, and agriculture. The second part analyses the interplay of mediators, networks, and learning by studying academic careers, travels, and collaborations within the British Empire, public internationalism in Geneva, the global transfer of corporate knowledge through expatriation, graduate mobility from the global south to the global north, and the international mobility of degree programs in higher education.This book is open access under a CC BY 4.0 license.